PENGEMBANGAN HYBRID LEARNING BERBASIS APLIKASI COMPUTER ASSITED TEST (CAT) PADA PROGRAM ARABIC PROFICIENCY TEST - Moh. Zulkifli Paputungan; Ana Mariana; Ibnu Rawandhy N. Hula (Tadbir: Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to develop Hybrid Learning based on the Computer Assisted Test (CAT) application in the Arabic Proficiency Test (APT) program.The method used was Research and Development with the ADDIE instructional design model (Analyze, Design, Develop, Implement and Evaluate), with development stages (concept, design, material collecting, assembly, testing and distribution). The results showed that the development of Hybrid Learning based on CAT application can be used in the Arabic Proficiency Test (APT) program which contains three language competency tests, (istima, tarakib and Qira’ah) and fulfills several aspects; 1) Self Instructional, 2) Self Instructional, 3) Self Contained, 4) Standalone, 5) User Friendly, and 6) Adaptive to technological developments. The results of the CAT-APT application trial in a limited group obtained a score of 80 (good) to 88 (very good), in the media validation test the score was 80 (good) to 86 (very good), the programming validation test and a score of 80 (good) to 88 (very good), while in the testing on the tester, the pretest score had not yet reached the advanced level, while in the posttest there were 9 testers who reached the advanced score.